Wyznaczniki finalnego komponentu recenzji muzycznej (na materiale polskim i amerykańskim) = The Polish-English Genre-Based Analysis of the Ending of Music Review - Wojciechowska, Anna; Majdańska-Wachowicz, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper reports on a contrastive genre-based study comparing Polish and American music reviews. The analysis concerns the structure of the texts in question. The material under investigation was collected from a Polish monthly "Teraz Rock" and an American, then, biweekly "Rolling Stone" (all issues from 2015). The objective of the paper is to indicate linguistic and non-linguistic constituents of the ending in music reviews. The data reveals that in both magazines the ending of the music review is a strategic position where communicative goals of this genre, especially evaluation, are strongly manifested. In addition, the ending of the review is aimed at shaping the recipient?s taste and creating a bond between the reviewer and readers.
Keywords: komponent finalny; recenzja muzyczna; struktura tekstu; genologia kontrastywna; ending; music review; text structure; contrastive genre-based studies